THE NEWEST INFANT NUTRITION CONCEPTS: POSTBIOTICS AND LONG-CHAIN POLYUNSATURATED FATTY ACIDS - S.L. Nyankovskyy; О.S. Nyankovska; M.S. Yatsula; M.I. Horodylovska (Bukovynian State Medical University, 2020)
Early life nutrition significantly impacts on growth and development as well as on health including elder ages. Postbiotics are compounds produced by microorganisms and released from food components or microbial constituents, including non-viable cells that, when administered in adequate amounts, promote health and well-being. Postbiotics: compounds deriving from bacterial metabolism, such as exopolysaccharides, vitamins, lactic acid, bacteriocins, enzymes, surfactants, antioxidants, and SCFAs; complex molecules released from food compounds (enzymatically produced during food fermentation), such as peptides and GOS, e.g., 3'GL and 6'GL; components released from lysed cells including DNA, RNA, cell walls and, perhaps, other cytoplasmic components, and surface layer proteins. Recently, a new fermentation technology has been developed for infant nutrition manufacturing. It uses two types of food-grade lactic acid producing microorganisms (Bifidobacterium breve C50 and Streptococcus thermophilus 065) that naturally delivering postbiotics. LCPUFAs have an important role in the immune system regulation, blood clots, neurotransmitters, cholesterol metabolism, and in the structure of membrane phospholipids in the brain and the retina. From February 2020, the new infant formulas standards have been in force in the European Union. They require the mandatory addition of docosahexaenoic acid at concentrations in two to three times higher than normal concentrations in human milk. New recipes of Nutrilon Premium+ infant milk formulas are the first and only fermented formulas that contains scGOS / lcFOS prebiotics (9:1, 0.8g / 100 ml), 3'GL postbiotic and the appropriate amount of omega-3  fatty acids in Ukraine's market at the present time.